Implementasi Pencatatan Keuangan Oleh Pengusaha Mikro-Kecil Di Kecamatan Ciputat - Ermalina Ermalina (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
The objectives of the study are to analyze the implementation of financial report (cash flow) by micro and small businesses in Ciputat Tangerang Selatan. The method used in this research is descriptive-qualitative. The result shows that the most of micro and small businesses of the (44.5%) do not have financial reports (cash flows). As for the rest, 33.3% of respondents have financial report and 22.2% of them make a report.